Concept Mapping and the CO-OP Approach with Adolescents with Autism Spectrum Disorder: Exploring Participant Experiences - Dr. Jessie Wilson; Dr. Angela Mandich; Dr. Lilian Magalhães; Dr. Kaity Gain (Scholarworks @ WMU, 2018)
Background: To explore the experiences of adolescents with ASD participating in a novel occupationally based intervention. Methods: The intervention used concept mapping in combination with the CO-OP approach with 10 adolescents with ASD in a 4 week program focused on developing life skills they deemed as important in their transition to adulthood. A descriptive qualitative approach was employed using deductive thematic analysis informed by Self-Determination Theory and occupationally relevant theoretical frameworks. This study is part of a larger feasibility project and focuses on the analysis of participant reflections and researcher field notes. Results: Five themes emerged: finding a sense of balance through negotiating tensions; a sense of "we" and a sense of "I"; selecting purposeful, meaningful, and authentic occupations; multimodal tools; and action through participating in doing. Conclusion: This study highlights valuable participant insights into their involvement in a novel occupationally based intervention that will inform the program's on-going development and implementation.